The Gender Representation, The Male and the Female Gothic in the work of The Mysteries of Udolpho by Ann Radcliffe - Ait Mechedal, Siham; ,Khalfa Sayah (University of Ammar Theledji -Laghouat, 2020)
The term gothic fiction refers to a style of writing that is characterized by elements of fear, horror, dread and gloom, as well as the romantic elements, such as nature individuality and very high emotions. These emotions can conclude fear, horror and suspense. The female and the male gender were represented differently in the gothic work The Mysteries of Udolpho, in which it was based on the themes of horror and terror to make a distinction between the two genders. Based on the descriptive analytical method to analyze and describe the ideas of the novel and rely on the gender representation that leads to the main reason of horror in the story. In the novel The Mysteries of Udolpho the female character or the heroine is represented as a courageous beautiful girl that was struggling with the oppression of the patriarch, as well she rebelled against the villain who imprisoned her by refusing his orders and in the end she could escape the prison of the villain who was represented as a strong cruel person who embodied the patriarchal society. He had authority over the female character by oppressing, torturing and imprisoning her. Yet in the end he was defied by the heroine. To force the reader to look directly at the horror depicted, rather than allowing them to become terrified by their own imagination is of course the technique of the horror literature as constructed with the terror gothic. All in all to let the readers know that the real horror in a gothic story is not always caused only by the supernatural elements yet it can be caused by the patriarchal suppression of woman